Desenvolvimento de nanocompósitos de blendas PA6/ABS compatibilizadas com copolímeros funcionalizados - Castro, Lucas Daniel Chiba de (2014)
Nanocomposites based on polyamide 6 (PA6) and acrylonitrile-butadienestyrene (ABS) blends compatibilized with styrene-maleic anhydride-acrylonitrile (SANMA) and methyl methacrylate-maleic anhydride (MA-MMA) were prepared by melt blending in a twin screw extruder through different mixing protocols. The nanoclay incorporation effect, different compatibilizing systems and components mixing sequence were evaluated in morphological, mechanical, thermal, thermomechanical and rheological properties. Evidences of chemical interactions between PA6 and reactive copolymers were observed by torque rheometry. XRD analysis indicates an exfoliated structure for all the nanocomposites due to the good interaction between PA6/OMMT. The significant increase in nanocomposites viscosity when compared with their respective ternary blends corroborates the results obtained by XRD. TEM micrographs show a strong influence of both reactive copolymers on polymer blends morphology, where the presence of SANMA and MMA-MA is responsible for reducing the dispersed phase particle size when compared to the uncompatibilized blend. TEM images confirm the existence of an exfoliation structure in all nanocomposites. The addition of both reactive copolymers significantly increased the ternary blends toughness when compared with PA6/ABS. Furthermore, the nanoclay incorporation enhanced the elasticity modulus and HDT of the nanocomposites but also reduced the toughness and the elongation at break when compared with their respective compatibilized blends.